2002
DOI: 10.1207/s15374424jccp3104_6
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Affectivity in Children: A Multitrait-Multimethod Investigation

Abstract: Examined the validity of the tripartite model of anxiety and depression and its internal structure in children. Measures of positive affect/surgency (PA/S) and negative affect/neuroticism (NA/N) and self-report and peer nominations of symptoms of depression and anxiety were completed by 104 children (mean age = 14.9 years, SD = 1.9). Parents completed measures of temperament and anxious and depressive symptoms. Multitrait-multimethod and confirmatory factor analyses (CFA) supported a 3-factor model that includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…Empirical studies show that emotionality (or emotional reactivity) is related to depressive symptoms, such that higher levels of negative emotionality predict more anxiety and depression (Anthony, Lonigan, Hooe, & Phillips, 2002;Phillips, Lonigan, Driscoll, & Hooe, 2002). Children with high negative emotional reactivity in first grade (approximately 6-7 years) had increasingly or consistently high levels of depression in early to middle adolescence (approximately 11-14 years; Brendgen, Wanner, Morin, & Vitaro, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies show that emotionality (or emotional reactivity) is related to depressive symptoms, such that higher levels of negative emotionality predict more anxiety and depression (Anthony, Lonigan, Hooe, & Phillips, 2002;Phillips, Lonigan, Driscoll, & Hooe, 2002). Children with high negative emotional reactivity in first grade (approximately 6-7 years) had increasingly or consistently high levels of depression in early to middle adolescence (approximately 11-14 years; Brendgen, Wanner, Morin, & Vitaro, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Cole et al [3] showed evidence of differentiation between depression and anxiety among sixth graders, but not among third graders, and reported poor construct validity, especially among the youngest children. Phillips et al [17] found that only self-reports of symptoms of anxiety and depression, and not parent-or peerreports, were related to self-reported negative affectivity in fifth through twelfth grade children. The authors stressed the need for parallel self-and parent-report measures to allow comparability of different reports.…”
Section: Methodsmentioning
confidence: 99%
“…The focus on the tripartite model in childhood and adolescence [12] has influenced the development of measures of positive and negative affectivity, such as the PANAS-C [17]. An important question is thus the extent to which the underlying disposition of negative affectivity influences the validity of depression and anxiety measures, and whether anxiety and depression should be assessed as separate traits.…”
Section: Overlap Between Symptoms Of Anxiety and Depressionmentioning
confidence: 99%
“…More recent research has supported the utility of all three constructs in children and adolescents in clinical (Joiner, Catanzaro, & Laurent, 1996;Joiner & Lonigan, 2000;Lonigan, Carey, & Finch, 1994) and nonclinical (Cannon & Weems, 2006;Olino, Klein, Lewinsohn, Rohde, & Seeley, 2007;Phillips, Lonigan, Driscoll, & Hooe, 2002) settings.…”
mentioning
confidence: 98%